RELATIONSHIP OF NUTRITIONAL STATUS AND AGE OF MENARCHE WITH THE INCIDENCE OF DISMENORE IN ADOLESCENTS AT SMP NEGERI 3 JEMBER - Vierna Nur Laili Febrianti (Fetus : Journal of Midwifery, 2023)
Reproductivehealth is important for adolescents, the initial change that occurs in adolescents is experiencing menarche, which can cause dysmenorrhea. The incidence of dysmenorrhea will increase with lack of nutritional status during menstruation. Method: This study used observation method with quantitative research design and through cross sectional approach and this study used Chi-Square test with sample taking using random sampling with a total of 126 populations and 56 as research samples. Study: Nutritional status ), is mostly in the normal BMI category (59.8% menarche age results are mostly in the >12 years category (73.7% ,) as a result of the incidence of dysmenorrhea, most respondents experienced dysmenorrhea as much as (89.9%). Analysis using the chis square test obtained p-value (0.00 < a (0.05) concluded that there is a relationship between nutritional status and the incidence of dysmenorrhea and there is a relationship between menarche age and the incidence of dysmenorrhea in adolescent girls at SMP Negeri 3 Jember. Conclusion: Imbalance of intake needs will cause nutritional problems in adolescents and cause dysmenorrhea. Advice: nutritional status in adolescent girls must be fulfilled properly because it will affect the growth and incidence of dysminore during menstruation.